The management scientist - Anderson, David Ray 1941- (South-Western College Pub., 2000)
Twelve menu-driven programs designed to solve a wide variety of quantitative models for managerial decision-making for students enrolled in quantitative methods and/or management science courses. Modules include linear programming, transportation, assignment, integer linear programming, shortest route, minimal spanning tree, PERT/CPM, inventory, waiting lines, decision analysis, forecasting, and Markov processes.